Comparison of the perioperative outcomes in antero-superior mediastinal tumor resection performed by transcervical resection and video-assisted thoracoscopic surgery - Zhu, Xin-Sheng; Song, Nan; Song, Nai-Cheng; Sihoe, Alan Dart Loon; He, Wen-Xin; Liu, Ming; Jiang, Ge-Ning; Zhang, Peng (Journal of Thoracic Disease, 2018)
Background: It remains controversial that whether transcervical resection (TC) was associated with better outcomes than video-assisted thoracoscopic surgery (VATS) in the treatment of antero-superior mediastinal tumors. We aimed to compare the safety and reliability between TC and VATS. Methods: Between 2010 and 2012, 80 consecutive patients underwent antero-superior mediastinal tumor resection via TC (n=31) or VATS (n=49). Perioperative outcomes were compared. A propensity score–matched analysis was performed to control the potential confounders. Results: A total of 41 men and 39 women with median age of 52.5 years were enrolled. No patient died during the perioperative course. After propensity matching, TC group was associated with less intraoperative blood loss (35.1±18.7 vs. 93.7±136.1 mL, P=0.034), less postoperative drainage (65.6±76.8 vs. 335.0±154.9 mL, P